Immune and inflammatory mechanisms of abdominal aortic aneurysm - Márquez-Sánchez, Ana Cristina; Koltsova, Ekaterina K. (Frontiers in Immunology, 2022)
Abdominal aortic aneurysm (AAA) is a life-threatening cardiovascular disease. Immune-mediated infiltration and destruction of the aortic wall during AAA development play an unexpectedly significant role in the pathogenesis of this disease. While various immune cells had been found in AAA, the mechanisms of their activation and function are still far from being understood. A better understanding of these mechanisms related to aberrant immune cell recruitment and activation in AAA is essential for novel preventive and therapeutic approaches. In this review, we summarize the current knowledge about the role of immune cells in AAA and discuss how pathogenic immune cell activation is regulated in this disease.